Pola pertumbuhan dan laju mortalitas Kepiting Bakau (jantan dan betina) jenis Scylla tranquebarica dan Scylla olivacea di Perairan Teluk Bintuni, Provinsi Papua Barat - Semuel Refideso; Ridwan Sala; Roni Bawole; Mudji Rahayu (Cassowary, 2023)
The purpose of this study was to determine the shape of the growth pattern of the relationship between carapace width and weight, growth parameters, and mortality and exploitation rate of mangrove crabs in the waters of Bintuni Bay Regency. This research was conducted in Teluk Bintuni Regency, West Papua Province. The sampling locations were spread in three locations, namely Bintuni, Manimeri and Babo. Mangrove crab samples obtained from fishing traps caught by fishermen in the waters of Bintuni Bay, identified gender (male or female), and measured carapace width and weight, then the measurement data were analyzed using the help of several data analysis formulas. Based on the results of the analysis, it is evident that the mangrove crab S. tranquebarica has a value of b = 3.6223 (male) with a positive allometric growth pattern and b = 2.8100 (female) with a negative allometric growth pattern, while the type of S. olivacea has a value of b = 2.8612 (male) and b = 2.1581 (female). The growth parameter values for male and female of S. olivacea were able to reach asymptotic carapace width (CW∞) = 20.90 cm, while males and females of S. tranquebarica (CW∞) = 18.90 cm and 19.21 cm, respectively. Natural mortality of S. tranquebarica in the waters of Bintuni Bay is estimated at 0.90 per year (male) and 1.31 per year (female), while S. olivacea is 1.02 per year (male) and 1.12 per year (female).